Pengaruh Model Pembelajaran Differentiated Instruction Berbantuan Media Baamboozle Terhadap Hasil Belajar Matematika Siswa Kelas V UPT SDN 064969 Medan - Siregar, Nela Suriani; Patri Jason Silaban; Ester Julinda Simarmata; Juliana; Dyan Wulansari HS (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Differentiated Instruction learning model assisted by Baamboozle media on the mathematics learning outcomes of fifth-grade students at UPT SDN 064969 Medan in the 2025/2026 academic year. This study employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest–Posttest Design. The sample consisted of 23 students from Class VB selected through purposive sampling. Data were collected through tests and questionnaires. The data were analyzed using the normality test, Product Moment correlation test, coefficient of determination test, and hypothesis testing (t-test). The results showed that the implementation of the Differentiated Instruction learning model assisted by Baamboozle media was categorized as very good, with a percentage score of 86.7%. The average student learning outcome increased from 46.22 on the pre-test to 85.69 on the post-test. The correlation test yielded a coefficient of 0.931, indicating a very strong relationship between the research variables. The coefficient of determination test produced an R Square value of 0.867, indicating that the Differentiated Instruction learning model assisted by Baamboozle media contributed 86.7% to students' learning outcomes. The hypothesis testing results showed that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Differentiated Instruction learning model assisted by Baamboozle media had a positive and significant effect on the mathematics learning outcomes of fifth-grade students at UPT SDN 064969 Medan in the 2025/2026 academic year.